PHYSIOLOGICAL RESPONSE OF LAMB TO ZINC SUPPLEMENTATION DURING HEAT STRESS SEASON - OMAR, DILMAN E.; BARWARY, MWAFAQ S. Q. (Journal of Duhok University, 2022)
The aim of this research was to evaluate the role of zinc supplementation on the reduction of heat stress in local lambs during hot season. In the current experiment, twenty-seven lambs were housed indoor in individual pens (1.50 × 1.30m). Zinc was added to the fresh drinking water in three different levels namely T1 (0 mg Zn/day), T2 (36 mg Zn/day) and T3 (72 mg Zn/day). Serum zinc (zinc; µmol/L), Alkaline phosphate (ALP; U/I), Alanine amino transferase (ALT; U/I), Aspartate amino transferase (AST; U/I), Creatine kinase (CK; U/I), Blood glucose level (mg/dl), Triiodothyronine hormone (T3; ng/ml), Thyroxin hormone (T4; ng/ml) were measured once per week. Zinc supplementation results show significant decrease in Aspartate amino transferase (AST) in (week 4), and Creatine kinase (CK) at (week 6) in T1group. Also zinc supplementation decreased triiodothyronine hormone (T3), and thyroxin hormone (T4) in (week 4). Whereas serum zinc level and alkaline phosphate (ALP) increased, also blood glucose level increased significantly in T2 (week 5) when the lambs were supplemented with 36 mg / zinc/ day. However, no effect of zinc supplementation was recorded on lamb serum ALT. Zinc supplementation was effective to increase blood plasma zinc concentration, ALP and kept the level of T4 from reduction during heat stress. However, zinc supplementation failed to keep the level of T3 from reduction during heat stress. This could be due to the type of zinc that was supplemented in the current experiment was inorganic which is less bioavailable than organic zinc